2022
DOI: 10.1186/s40798-022-00455-6
|View full text |Cite
|
Sign up to set email alerts
|

Women Have Tendons… and Tendinopathy: Gender Bias is a “Gender Void” in Sports Medicine with a Lack of Women Data on Patellar Tendinopathy—A Systematic Review

Abstract: Introduction Patellar tendinopathy is one of the most common musculoskeletal problems associated with sport. While commonly perceived as a predominantly male problem, recent epidemiological studies revealed that it also affects a large number of sport-active women. The aim of this systematic review was to understand how the available treatments apply to women affected by patellar tendinopathy. Methods We analysed the available literature with a sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Men and women present numerous physiological and pharmacological differences, and male overrepresentation could influence the understanding of efficacy of a specific injection treatment in women, as already reported for injective treatments in the general population [20, 32]. In this light, there is a need for greater representation of women in studies and the reporting of sex‐stratified data in order to understand if there are different risks and different clinical outcomes with injective treatments in sport‐active women [20, 39]. This and other aspects of the treated patients and of the products should be investigated to optimize the use of injective treatments in sport‐active patients affected by knee degenerative cartilage lesions or OA.…”
Section: Discussionmentioning
confidence: 99%
“…Men and women present numerous physiological and pharmacological differences, and male overrepresentation could influence the understanding of efficacy of a specific injection treatment in women, as already reported for injective treatments in the general population [20, 32]. In this light, there is a need for greater representation of women in studies and the reporting of sex‐stratified data in order to understand if there are different risks and different clinical outcomes with injective treatments in sport‐active women [20, 39]. This and other aspects of the treated patients and of the products should be investigated to optimize the use of injective treatments in sport‐active patients affected by knee degenerative cartilage lesions or OA.…”
Section: Discussionmentioning
confidence: 99%
“…Sex and gender bias in SEM settings are evident in multiple ways. Systematic reviews demonstrated that female athletes are under-represented in sports and exercise research 1 2. International Olympic Committee consensus statements identified the need for increased representation and inclusion of authors from different genders, ethnicities, skill sets and levels of experience 3.…”
Section: Female Under-representation In Semmentioning
confidence: 99%
“…Disparities in funding and resources for professional female athletes not only lead to a gender data gap in research but also result in less access to high-quality sports medical care, diagnostics and strength and stability coaches. Furthermore, a lack of data on injury prevention programs among women in competitive sports still exists [ 2 ]. Specialists in sports medicine, as well as menstrual health management and mental health specialists, are necessary in a female athlete’s career to address early issues such as pre-menstrual syndrome or pregnancy-related concerns.…”
Section: Introductionmentioning
confidence: 99%